2021
DOI: 10.1021/acsmaterialsau.1c00042
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Spherically Super-Structured Polyamides for the Sustainable Water Remediation

Abstract: Unlike metal-ornamented hybrid material and linear polymers, we invoked the growth of a biodegradable superstructured cross-linked polyamide-ester material. The material is thermally stable. The thiol-alkene photoclicked material acted as an efficient water remediator. The material efficiently monitored amphiphilic dyes like rhodamine B (RHB), methylene blue (MB), and chronic mercuric ions in water. The adsorption kinetics revealed the material could adsorb >95% dyes within 24 h. The RHB-functionalized polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 37 publications
(72 reference statements)
0
14
0
Order By: Relevance
“…Kumer et al reported the utilization of thiol‐alkene and thiol‐alkyne Click reaction for the growth of adsorbant 13–15 . Moreover, Kumar et al reported the method to grow unique morphology for the material which acted a mercury chemosensor 16 . The proposed model is to engineer metal free organic crosslinked polymeric material which will be water immiscible and easy to handle.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kumer et al reported the utilization of thiol‐alkene and thiol‐alkyne Click reaction for the growth of adsorbant 13–15 . Moreover, Kumar et al reported the method to grow unique morphology for the material which acted a mercury chemosensor 16 . The proposed model is to engineer metal free organic crosslinked polymeric material which will be water immiscible and easy to handle.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Moreover, Kumar et al reported the method to grow unique morphology for the material which acted a mercury chemosensor. 16 The proposed model is to engineer metal free organic crosslinked polymeric material which will be water immiscible and easy to handle. To do so we have taken initiative to grow hydrothiolated clicked polymer film with input of stoichiometric quantity of fluorescent functional PAHs-naphthalene and pyrene unit as dopant into the crosslinked polymeric film via facile thiol-alkene and thiol-alkyne Click reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The engineered material is proposed to be a metal‐free organic crosslinked polymeric material, which will surely be eco‐friendly, water‐immiscible and easy to handle. To do so, we have taken the initiative to grow hydrothiolated clicked polymer film with the input of a stoichiometric quantity of fluorescent naphthyl unit as a dopant into the crosslinked polymeric film via facile thiol‐alkene and thiol‐alkene‐alkyne Click reaction [13–20] . The static aggregated photoluminescent units within the material is expected to initiate photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Kumar et al reported crosslinked super structured poly(amide) for adsorption of dyes-rhodamine B and methylene blue too. [7] Kumar et al reported the encapsulation and release of fluorescent dye with degradable metal free organogel. [8] The reports on metal ornamented materials, poly(ester), and poly(amide) seems to be explored more compared to polyurethane based material.…”
Section: Introductionmentioning
confidence: 99%